Design and demonstration of a 400 Gb/s indoor optical wireless communications link - Gomez, A; Shi, K; Quintana, C; Maher, R; Faulkner, G; Bayvel, P; Thomsen, B; O'Brien, D (Institute of Electrical and Electronics Engineers, 2016)
In this paper we report an ultrafast transparent fibre-wireless-fibre link for indoor optical wireless communications. The link operates over ~3 m range at 416 Gb/s and 208 Gb/s with a wide field of view (FOV) of 40° and 60°, respectively. The system design is fully characterized in simulations, which are in good agreement with the experimental data. To the best of our knowledge, this is the fastest demonstration of an indoor wireless link that offers practical room-scale coverage.